2023
DOI: 10.1289/ehp11248
|View full text |Cite
|
Sign up to set email alerts
|

Transportation Noise and Risk of Tinnitus: A Nationwide Cohort Study from Denmark

Abstract: Background: There is a growing body of evidence linking residential exposure to transportation noise with several nonauditory health outcomes. However, auditory outcomes, such as tinnitus, are virtually unexplored. Objectives: We aimed to investigate the association between residential transportation noise and risk of incident tinnitus. Methods: We conducted a nationwide cohort study including all residents in Denmark age , of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…The general understanding is that noise exposure below 80 dB(A) cannot harm hearing. However, a recent nationwide study from Denmark found that exposure to road traffic noise was associated with higher risk of tinnitus with adjusted HR of 1.06 (95 % CI: 1.04; 1.08) and 1.02 (95 % CI: 1.01; 1.03) per 10-dB increase in 10-year exposure to L den Min and L den Max, respectively [ 11 ]. The highest HRs were found among people without hearing loss and among those who had never been in a blue-collar job.…”
Section: Health Impact Of Transportation Noisementioning
confidence: 99%
See 3 more Smart Citations
“…The general understanding is that noise exposure below 80 dB(A) cannot harm hearing. However, a recent nationwide study from Denmark found that exposure to road traffic noise was associated with higher risk of tinnitus with adjusted HR of 1.06 (95 % CI: 1.04; 1.08) and 1.02 (95 % CI: 1.01; 1.03) per 10-dB increase in 10-year exposure to L den Min and L den Max, respectively [ 11 ]. The highest HRs were found among people without hearing loss and among those who had never been in a blue-collar job.…”
Section: Health Impact Of Transportation Noisementioning
confidence: 99%
“…Tinnitus symptoms are likely enhanced in stressful periods, where stress hormones can affect the limbic, reticular, and auditory systems, as negative thoughts towards tinnitus affect the ability to habituate to the symptoms [ 164 , 165 ]. Cantuaria et al demonstrated the highest HRs for L den Min, a potential proxy for nighttime noise exposure [ 11 , 166 ]. Stress and tinnitus may form a vicious circle as sleep deprivation increases stress, which has negative impact on tinnitus [ 167 ].…”
Section: Health Impact Of Transportation Noisementioning
confidence: 99%
See 2 more Smart Citations
“…Several research reports have linked long-term exposure to traffic noise with various health issues, including hearing loss [7,8], cardiovascular disease [9,10], sleep disturbances [11][12][13], and impaired cognitive function [14]. Moreover, traffic noise can result in annoyance [15], stress [16], and tinnitus [17]. Overall, it is clear that traffic noise can significantly reduce the overall quality of life for residents.…”
Section: Introduction 1backgroundmentioning
confidence: 99%